BENTUK PERJANJIAN BAGI HASIL TANAH PERTANIAN KAITANNYA DENGAN UNDANG-UNDANG NOMOR 2 TAHUN 1960 TENTANG PERJANJIAN BAGI HASIL DI DESA PEGUYANGAN KANGIN - Trian Dhana, Ida Bagus; Sarjana, I Made (Kertha Wicara : Journal Ilmu Hukum; Vol. 04, No. 01, Februari 2015)
This journal discusses the form of agricultural land sharing agreement relation with Law Number 2 About 1960 Revenue Sharing Agreement in Peguyangan Kangin village. In Article 3 of Law Number 2 About 1960 Revenue Sharing Agreement governing the form of an agreement that requires the parties to this agreement agricultural landowners and tenant farmers make an agreement in writing made before the head of the village, include at least 2 witnesses each of the parties, as well as the agreement ratify before the sub-district heads. The problem faced is: how is the form of profit sharing agreements are used by the people in the village Peguyangan Kagin in making arrangements for the resultsof agricultural land?The results of the research conducted, it can be seen that the form of agricultural land sharing agreements are used by the people in the village Peguyangan Kangin is no written agreement.
Keywords: Form of Agreement, Revenue Sharing, Agricultural Land